W.E. Clyde Todd (1875-1969) - Woods, Jr., Lawrence C. (ARCTIC, 1969)
. Since the age of fifteen Clyde Todd gave his life to the field of ornithology, a vocation he had chosen at even an earlier age as a small boy in a rural community of Western Pennsylvania. . In 1899 his association with the Carnegie Museum of Pittsburgh began - one which lasted seventy years until his death in June 1969. Although retired in 1945 as Curator of Ornithology, Mr. Todd continued to work at the Museum, writing, studying, and classifying its vast collection of birds and their eggs. . Although his study of birds in Western Pennsylvania occupied much of his life and led to the publication of his second outstanding work, The Birds of Western Pennsylvania, in 1940, it was the subarctic regions of eastern Canada to which he turned repeatedly and with ever increasing enthusiasm and interest. Carnegie Museum, over a period of nearly sixty years, sent twenty-five expeditions to the Labrador Peninsula and northeastern Ontario, on twenty of which Mr. Todd was a participant. The journeys were made, as he enjoyed saying, "the hard way" - that is, by canoe, sailing sloop, by sled, or afoot. The purpose of the many trips in which he participated, and others which he directed, was to map the range of birds in that vast area and to ascertain the character and extent of their natural life zones. The result of his observations and collections culminated in 1963 in the publication of his monumental work, The Birds of the Labrador Peninsula and Adjacent Areas, published by the University of Toronto Press in cooperation with Carnegie Museum, and with the generous help of grants from Mrs. Alan M. Scaife and Edward O'Neil, both of Pittsburgh. It was hailed as the finest bird book ever produced in Canada. More than eight hundred pages in length, this volume is descriptive of over three hundred species, illustrated with many photographs taken on various expeditions and with magnificent colour plates by Dr. George M. Sutton, who accompanied Mr. Todd on several of his journeys. . Space does not permit a detailed account of Mr. ...